Comparative Efficacy of Subcutaneous Versus Intravenous Interleukin 12/23 Inhibitors for the Remission of Moderate to Severe Crohn’s Disease: A Systematic Review and Meta-Analysis - Nouran Alwisi; Rana Ismail; Hissa Al-Kuwari; Khalifa H. Al-Ansari; Mohammed A. Al-Matwi; Noor A. Aweer; Wejdan N. Al-Marri; Yousif Al-Kubaisi; Muneera Al-Mohannadi; Shahd Hamran; Suhail A. R. Doi; Habib H. Farooqui; et al. (Biomedicines)
Background/Objectives: Interleukin 12/23 inhibitors are a newer class of monoclonal antibodies used to induce and maintain remission for Crohn’s disease (CD), a chronic inflammatory bowel disease, when patients do not respond to conventional immunomodulatory drugs or first-line monoclonal antibody therapies. Although biologics are best administered intravenously, subcutaneous administration has been trialed, with mixed results. This research synthesized evidence on the efficacy and safety of subcutaneous compared to intravenous administration of interleukin 12/23 inhibitors for moderate to severe CD. Methods: In this systematic review and meta-analysis, we searched Cochrane, PubMed, SCOPUS, CINHAL, and preprint archives for randomized controlled trials (RCTs) that compared the efficacy and safety of subcutaneous to intravenous interleukin 12/23 inhibitors for the remission of CD. After study quality assessment, a meta-analysis was carried out using a bias-adjusted inverse variance heterogeneity model, heterogeneity was assessed using I2, and publication bias was performed using Doi plots. Evidence certainty was assessed using Grading of Recommendations, Assessment, Development, and Evaluations (GRADE). Results: Seven RCTs, with 2179 participants, all with moderate to severe CD, were included. After meta-analysis, subcutaneous compared to intravenous administration showed similar efficacy for the induction of remission (OR 0.77, 95%CI 0.53–1.12), with no-to-low heterogeneity (I2 = 0%, p = 0.97). For the maintenance of remission, only two studies had analyzable data, and they showed that subcutaneous interleukin 12/23 inhibitors were equal or better compared to intravenous administration. Further syntheses showed that subcutaneous compared to intravenous administration of interleukin 12/23 inhibitors had almost similar odds of adverse events (OR 0.91, 95%CI 0.63–1.32, I2 = 39%), serious adverse events (OR 0.97, 95%CI 0.61–1.53, I2 = 0%), and treatment discontinuation (OR 1.06, 95%CI 0.67–1.68, I2 = 0%). Conclusions: In individuals with moderate to severe CD, subcutaneous administration has similar efficacy for inducing remission with comparable safety. More RCTs are needed to confirm these findings.